Qur’an Versus Kabbalah: A Reading into Palestinian-Israeli Conflict - Asmad, Arman; Amin, Elsayed Mohamed Abdalla; Ahmed, Mohamed Mohi El-Din; Youssef , Ahmed (Journal of Al-Tamaddun, 2025)
This paper examines the historical development of Messianic Kabbalah and its impact on the Palestinian–Israeli conflict. It argues that the concept of redemption (tikkun), a central theme in Messianic Kabbalah, has been a significant factor in the conflict and has contributed to using force for peace. It provides a detailed analysis of the historical evolution of Messianic Kabbalah and its role in shaping the religious and political beliefs of different Jewish groups, including the Zionist settlers. It also examines the theological and philosophical foundations of Messianic ideas, which helped to establish beliefs that influenced the development of Zionism, and uses a historical-critical methodology to analyse Jewish sources in the Qur’an. It focuses on 20th-century figures like Gershom Sholem and Rabbi Abraham Isaac Kook rather than earlier Zionist figures (e.g., Rabbi Yehudah Alkalai, Rabbi Hirsch Kalischer, Ahad Ha’am, Rabbi Mohilever, Jacob Klatzkin). Sholem’s pioneering analysis of Jewish mysticism and Kook’s synthesis of Messianic Kabbalah with Zionist ideology together illuminate how mystical ideas were transformed into modern political practices. This approach contrasts with the works of other Kabbalistic authorities such as Jacob Emden, Leon Modena and non-Jewish scholars like Johannes Buxtorf, Jean Morin and Jacques Basnage, whose contributions are less directly connected to the evolution of Zionist thought. The study opens the door for future research to explore the lesser-known aspects of Islamo–Judeo relations during the 12th century. The main findings of this paper pave the way towards a better understanding of the intricate relationship between religion, politics and violence in the Palestinian–Israeli conflict through the framework of the Qur’an and, specifically, how the displacement of Palestinians witnessed in modern times can be traced back to Messianic ideas. Zionism adopted Kabbalistic Messianism to justify colonialist ideologies. The theological interpretation of Messianic Kabbalism is developed in isolation of the Qur’anic interpretation and Islamic influence.